Exploiting of Wasted Cooking Oil at Making Biodiesel Through Transesterification Process With Applies K2CO3 Catalyst as Fuel Diesel of Renewable - ST.,M.T., Zulkarnain (KINETIKA, 2011)
This research aim is to know the influence from various usage of K2CO3 catalyst and methanol solvent to biodiesel from wasted cooking oil. The making of biodiesel from waste cooking oil as raw material this before all was done by using esterification process with purpose to reduce %FFA >5% become < 5% with some help of the same solvent that is methanol and K2CO3  catalyst, then is continued to phase herein after is processing transesterification. The tranesterification process if wasted cooking oil in methanol to yield biodiesel applies alkaline catalyst. Sighting of % K2CO3  and methanol volume to product biodiesel need to be done to get product biodiesel fulfilling standart.  Process tranesterification of wasted cooking oil using alkaline catalyst (K2CO3 ) and methanol solvent is done with various % K2CO3  that 0,1%, 1.0%, 1.5% and methanol equel to 15 ml, 20 ml , 25 ml. This research done by the way of mixing wasted cooking oil , methanol and K2CO3  in neck gourd four with operating condition 70 oC during 1 hour and result of his it?s dissociated in separatory funnel then is hushed during 24 hour. From the research was received by the optimum condition in the use K2CO3 with concentration 0.5% wt and the volume of methanol 1250 ml. Result of the analysis of physical characteristics and chemistry biodiesel that was received % rendemen 56,07%, density 0,852 gr/ml, pH 7,1, acid number 0,53 of mgKOH, flashpoint 168 oC, % water content 0.03%, viscosity 3.09 cSt and calories value 6374.54 cal/gr. The biodiesel product that have got has been fulfill the Indonesian standard biodiesel quality.